Learners’ Perceptions of Using YouTube Videos in Enhancing Their Communication Skills - Maphanga Nhlakanipho; Mogale Simon Maeko Albert; Nkwanyane Themba; Ramaboea Hendrick; Praygod Nkosi; Kola Malose Isaac (Indonesian Journal of Education and Social Studies, 2025)
Integrating YouTube videos in teaching and learning has transformed teaching pedagogies by offering educators a powerful tool for enhancing learning experiences. This study focused on using YouTube videos to enhance the teaching and learning of communication skills when executing their mini-Practical Assessment Tasks. In addition, the study intended to have a better grasp of how learners perceive the employment of YouTube videos to support them in improving their communication skills. This study adopted qualitative research as a research approach to gather non-numerical data. Hence, a case study was used in the research design to explore the effectiveness of using YouTube videos to enhance grade 9 Technology learners’ communication skills during the execution of mini-Practical Assessment Tasks. Observations and semi-structured interviews were used to gather data. Inductive analysis was used to analyse the data obtained from the semi-structured interviews while thematic content analysis was used to analyze the data gathered through observations. The researchers identified YouTube videos as effective in enhancing learners’ communication skills. The study also found that some learners were not focusing during the presentation, which could be influenced by the fact that learners in rural areas still prefer the traditional way of teaching.